Jual Beli Sebagian Tanah yang Dijaminkan ke Bank - Asha Azela Aqilla Andias; Nynda Fatmawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study focuses on examining the legal status of buying and selling certified land that is guaranteed by debt, about this very much happens in the community which causes a lot of confusion. This study refers to the Agrarian Law, namely Law Number 5 of 1960. This research is expected to be able to answer some of the problems that occur regarding (1) forms of legal protection that are devoted to the buyer and seller, and (2) an analysis of the position of the sale and purchase of land that is certified but is still guaranteed by the debts. This study uses a normative method and uses a statutory approach. The results showed that land that is still collateralized by the bank can be purchased by "redeeming" the certificate at the relevant bank. That is, the buyer can pay the bank the amount required by the bank to be released as collateral for repayment of the seller's debt.